Guilt : a mystery - Higashino, Keigo, 1958- (Detective Godai, 2026)
"Homicide Detective Godai of the Tokyo Metropolitan Police Department is assigned to investigate the death of a lawyer, Kensuke Shiraishi, whose body was found on a Central Tokyo riverbank. His investigations leads him to one Tatsuro Kuraki, who claims to have had limited contact with Shiraishi - but, surprising the investigators, Kuraki not only confesses to the lawyer's murder, but another one from thirty years ago - for which another man was arrested and died in custody before trial. This brings unexpected resolution to two cases but there is one problem: to Detective Godai the confession rings false. And Godai is not the only one who cannot accept Kuraki's explanation of both murders and his professed motives. The confessed murderer's son and the victim's daughter both feel strongly that both the act and the motive claimed are untrue. As Godai investigates further, he discovers that the relation between the murder of thirty years ago and the recent one is complex, raising multi-faceted questions of guilt and innocence"-- Provided by publisher.